2018
DOI: 10.1038/bjc.2017.447
|View full text |Cite
|
Sign up to set email alerts
|

Human ex vivo prostate tissue model system identifies ING3 as an oncoprotein

Abstract: Background:Although the founding members of the INhibitor of Growth (ING) family of histone mark readers, ING1 and ING2, were defined as tumour suppressors in animal models, the role of other ING proteins in cellular proliferation and cancer progression is unclear.Methods:We transduced ex vivo benign prostate hyperplasia tissues with inducible lentiviral particles to express ING proteins. Proliferation was assessed by H3S10phos immunohistochemistry (IHC). The expression of ING3 was assessed by IHC on a human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
5
30
1
Order By: Relevance
“…ING3 expression is lost or reduced in human tumors 8 and a higher mortality has been associated with a decreased expression of ING3 38,39 . Two recent studies suggest that ING3 could act as an oncogene in prostate cancer 40,41 but mainly, ING3 has been shown to exert tumor suppressor functions as a gatekeeper. Thus, ING3 modulates p53-mediated transcription and regulates apoptosis in melanoma cells in response to UV 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…ING3 expression is lost or reduced in human tumors 8 and a higher mortality has been associated with a decreased expression of ING3 38,39 . Two recent studies suggest that ING3 could act as an oncogene in prostate cancer 40,41 but mainly, ING3 has been shown to exert tumor suppressor functions as a gatekeeper. Thus, ING3 modulates p53-mediated transcription and regulates apoptosis in melanoma cells in response to UV 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of ING3 in the cell cycle is more ambivalent because in some cases ING3 could induce rather than inhibit cell growth, as it has been observed in the Yng2 mutant yeast that harbors a mitotic delay [35]. Indeed, an increase in the expression of ING3 has been shown to correlate with proliferation in rapidly proliferating and rapidly replenishing cells such as those in the small intestine, bone marrow and epidermis [81], but also to increase the levels of proliferation marker when it is overexpressed in prostate cancer cells [70]. In the same study, the exogenous expression of ING3 increases colony formation; a result which corroborates what was observed in our recent study where the tumor cells downregulated for ING3 exhibited a reduced capacity for colony formation under physiological conditions (without genotoxic treatment) in both yeast and human cells [82].…”
Section: Ing3 In Cell Cycle Regulationmentioning
confidence: 99%
“…Evidence has shown that ING3 participates in the regulation of the cell cycle because its overexpression leads to proliferative defects [67][68][69][70]. Like other ING members, ING3 was found to negatively regulate cell growth in a p53-dependent manner since its overexpression not only inhibited cell proliferation but also colony formation, except in cells inactivated for p53 [19,36,67,[71][72][73].…”
Section: Ing3 In Cell Cycle Regulationmentioning
confidence: 99%
“…It is considered a strong tumor-suppressor candidate gene due to its role in ATM signaling and DNA repair, preventing cancer initiation and progression [56], in addition to promoting cell cycle arrest and apoptosis by blocking the PI3K/AKT pathway in gastric cancer [57]. In contrast, other studies have reported that ING3 acts as an oncoprotein, stimulating tumor growth and activating the androgen receptor in prostate cancer [58,59]. A role in monocyte to dendritic cell differentiation was also reported due to targeting of ING3 by miR-21 [60].…”
Section: Ing3: a Distinguished Member Of The Ing Familymentioning
confidence: 99%